A multiple synergistic composite coating with ultrahigh anti-corrosion performance under harsh oxygen environment. (November 2022) - Yu, Chao; Zhang, Meng; Xu, Fei; Meng, Lei; Wei, Yuting; Chang, Yuanyuan; Zhang, Meng; Fu, Dengyu; Wang, Huaiyuan
Abstract: Designing effective strategies to satisfy the anti-corrosion requirements in high-pressure oxygen and high salt environment still remains a huge challenge. Herein, the oriented polyaniline nanofibers doped with phytic acid were synthetized on the surface of sericite (PPANI-Ser) by in-situ polymerization to endow epoxy coating with ultrahigh anti-corrosion performance. The |Z|0.01 Hz of PPANI-Ser/EP coating immersed in 12 wt% NaCl solution still maintained above 10 11 ohm⋅cm 2 after 90 days of immersion at 60 °C. Significantly, after 10 days immersion in the coupling environment of 3 MPa pure O2 and 12 wt% NaCl solution, PPANI-Ser/EP coating had almost no deterioration. Graphical Abstract: ga1 Highlights: Oriented PANI nanofibers doped with PA were synthesized on the surface of Ser by in-situ polymerization. The interfaces between PPANI-Ser and resin are more compact, which will significantly enhance the impermeability performance. PPANI-Ser combined the barrier property of Ser, the passivation function of PANI and the chelation function of PA. PPANI-Ser/EP coating exhibits ultrahigh anti-corrosion performance in high-pressure oxygen and high salt environment.